Naturjodel und Emotion Interdependenzen mit Fokus auf Unterwalden - Kammermann, Andrea (innsbruck university press, 2022)
This study investigated the emotional experiences of yodelers and listeners in relation to a specific type of yodeling, practiced in Unterwalden, a region in Central Switzerland. The yodels of Unterwalden are based on a local repertoire, sung with a complex vocal technique that focuses on syllabic pitch change. Across three consecutive studies was explored how yodelers and listeners experienced different evocations and felt emotions in connection with the yodels of Unterwalden. Reported are herein a) the characteristics of strong experiences with yodel including positive feelings, physiological reactions, a loss of control while being touched by the music, and aspects of enhanced socialization within the community, b) an evaluation of selected audio samples illustrating that the yodels of Unterwalden preferentially evoke certain sensations, such as a balanced relationship between sublimity and vitality, and c) that contextual and personal factors, as well as the musical structure, the type of polyphony, and the characteristic timbres of the yodel voices have a decisive influence on the emotional intensity experienced.